Determinants of E-Commerce Adoption for Saudi MSMEs: Does E-Commerce Adoption Impact Financial and Non-Financial Performances? - Alharthi, Majed; Islam, Md. Mazharul; Ben Hamida, Abdel Ghaffar; Dash, Ganesh; Murad, Md. Wahid (International Journal of Economics and Financial Issues, 2025)
Recently, business operations and performance for micro, small, and medium-sized enterprises (MSMEs) around the world have been impacted from the COVID- 19 spread. To sustain their businesses, many strategies have been adopted and implemented from the MSMEs. This study examines and analyzes the correlation between e-commerce adoption (ECA) and the performance of MSMEs in Saudi Arabia and identifying the drivers that influencing ECA over the period of COVID- 19 pandemic. The data in this study were collected from 513 MSMEs across different regions of Saudi Arabia. Statistically, the data were examined utilizing the partial least squares-structural equation modeling (PLS-SEM) method to evaluate the proposed model. The results indicated that technology resources, technical infrastructure, and company size are critical factors influencing e-commerce adoption. The use of e-commerce was strongly correlated with both the financial and non-financial success of MSMEs during the period of COVID- 19. Additionally, MSMEs found being as a mediator for the association between ECA and the financial performance. The results of this study added to the knowledge and contribute to the existing literature review of technology adoption through analyzing the determinants of ECA and the e-commerce’s role in performance of firm during a global pandemic. The results are valuable for MSME managers and policymakers, highlighting the critical significance of e-commerce implementation for business growth and long-term continuation. Policymakers can also use these findings to develop policies and strategies for promoting e-commerce application in Saudi Arabia. Furthermore, this study provides a significant contribution to the development of the framework of Technology-Organization-Environment (TOE) for MSMEs.